Determination of the Shelf Life of an Extract and Microencapsulated Lycopene Obtained from Agro-Industrial Waste of Tamarillo (Solanum betaceum) - Fernández Rivero, Danae (2025)
Stability studies were conducted to evaluate the shelf life of the lycopene extract and microencapsulated lycopene, following the guidelines established in ICH Topic Q1A (R2), (2003). The main objective was to estimate the product's stability period under the defined storage conditions, ensuring its quality and functionality over time. For the lycopene extract, storage in amber glass bottles was used to protect it from light and reduce its exposure to oxygen. This extract was maintained at controlled temperatures of 2 to 8°C for a period of 15 days. During this time, periodic analyses were carried out to determine the lycopene concentration and evaluate its stability. In the case of microencapsulated lycopene, a different storage system was used, employing high-density polyethylene bags with aluminum. These packaging conditions provide greater protection against moisture, light, and oxygen, which enhances the compound’s stability. This product was stored at a temperature of 20 ± 5°C for a period of 24 months. The shelf life of both products was determined based on the analysis of lycopene concentration over time, allowing for the assessment of compound degradation under specific storage conditions. Additionally, at the end of the study, antioxidant activity was evaluated using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) technique. The results indicated that the lycopene extract had an estimated shelf life of 7 days when stored in amber glass bottles at temperatures of 2 to 8°C. On the other hand, the microencapsulated lycopene showed greater stability, reaching a shelf life of 22 months when stored in high-density polyethylene bags with aluminum